In the name of the stakeholder: An assessment of representation surpluses and deficits by nonprofit leaders - Peter Schubert; Jurgen Willems (Nonprofit Management and Leadership, 2021)
Nonprofit leaders face the challenge of making decisions within a complex environment of heterogeneous and often competing stakeholder claims. In such a setting, leaders not only make judgments about the power of their organization's stakeholders but they also make conscious choices about which stakeholders they personally represent while making organizational decisions. This study uses insights from stakeholder theory and agency theory to investigate (1) how nonprofit leaders' perceptions of stakeholder power and stakeholder representation are interrelated across a wide range of stakeholder groups and organizations, and (2) how perceptions of power and representation differ between board members and executive managers. Drawing on data from 491 nonprofit leaders, we find evidence of stakeholder representation surpluses and deficits for several stakeholders, although perceptions of these deficits and surpluses differ considerably between board members and managers. Our study holds important implications for nonprofit governance, the practice of stakeholder analysis, and the use of stakeholder constructs in future empirical research.
Keywords: 650; common agency; quantitative-exploratory; stakeholder power; stakeholder representation; stakeholder theory